Mechanism of anterior cruciate ligament injuries in soccer - Fauno, P.; Wulff Jakobsen, B. (International Journal of Sports Medicine, 2006)
One hundred and thirteen patients, consecutively admitted to our clinic with an anterior cruciate ligament (ACL) rupture sustained while playing soccer, were surveyed and the mechanism behind their injury analyzed. The diagnosis was made arthroscopically or by instrumented laxity testing. The findings showed that the vast majority of the injuries were of the non-contact type and that very few were associated with foul play. No player positions were over- or underrepresented and goal keepers are apparently just as prone to ACL injury as their teammates. The findings of this study have helped our understanding of the mechanism behind ACL injuries in soccer and could be an aid to establishing future prophylactic measures. The findings also emphasize that certain injury mechanisms on the soccer field should alert the physician and draw his attention to a possible ACL injury.